Hand‐spinning chrysotile exposure and risk of malignant mesothelioma: A case–control study in Southeastern China. Issue 3 (10th October 2017) - Jiang, Zhaoqiang; Chen, Tianhui; Chen, Junqiang; Ying, Shibo; Gao, Zhibin; He, Xianglei; Miao, Chao; Yu, Min; Feng, Lingfang; Xia, Hailing; Wu, Wei; Chen, Riping; et al.
Abstract : While chrysotile has been commonly used by Chinese textile industry for many years, investigations on the association of chrysotile exposure with risk of mesothelioma in China are scarce. We conducted a case–control study in a county located at Southeastern China, including 46 cases and 230 individually matched controls. A semi‐quantitative method based on experts' assessment was used for evaluating hand‐spinning chrysotile exposure. Conditional logistic regression models were used to assess the association of asbestos exposure with risk of mesothelioma. We found that hand‐spinning chrysotile exposure was associated with significantly elevated risk of mesothelioma, reaching OR =10 (95% CIs: 1.4–65) for possible exposure and 64 (12–328) for definite exposure. Our data suggested a dose–response relationship of chrysotile exposure duration with risk of mesothelioma, reaching 28 (6–134) for <6 years, 51 (11–247) for 7–17 years and 56 (9–351) for ≥18 years. A dose–response relationship of cumulative exposure index (CEI) with risk of mesothelioma was found, reaching 28 (6–137) for CEI at 0–0.5 fibers per milliliter years (f/mL‐year), 36 (7–184) for CEI at 0.5–28.6 f/mL‐years and 79 (14–451) for CEI > 28.6 f/mL‐years. We found a dose–response relationship of chrysotile exposure duration and CEI with risk of mesothelioma in Southeastern China, adding valuable information on health hazards of chrysotile exposure in China where chrysotile is still used nationwide. Abstract : What's new? While chrysotile has been commonly used by the Chinese textile industry for many years, the association of exposure to this form of asbestos with risk of mesothelioma in China has been scarcely investigated. Here, the authors investigate the association of chrysotile exposure (through hand‐spinning in manufacturing plants or at home) with risk of malignant mesothelioma in Southeastern China in a study where the majority of cases were women. They found dose–response relationships of exposure probability, intensity, frequency, duration and cumulative exposure index with risk of mesothelioma. The study adds valuable information on health hazards of hand‐spinning chrysotile exposure in China.